Effect of exercise with elastic cord on postural stability in a group of elite gymnasts - Struhár, I.; Dovrtelová, L.; Kapounková, K. (Journal of Human Sport & Exercise, 2014)
The main aim of this study was to find out if exercise with elastic cord improved postural stability in a group of elite gymnasts. For measuring postural stability an electronic balancing board with variable radius and integrated feedback was used. The exercise regimen was undertaken twice a week for 12 weeks. All participants were measured at the beginning of our study and then after 12 weeks. Participants had to stand on the electronic balance board during 30 seconds with open eyes and kept the board balanced using feedback from the screen. After that we compared the results of each participant. The results were expressed by number from 0 to 100. Twenty-nine elite gymnasts volunteered for this study. Participants did not report any neuromusculoskeletal injuries or other diseases that may affect balance performance. Before participating in the study, all parents of gymnasts read and signed the informed consent form. The participants were assigned to a control group (15 girls; mean age=13.78±1.62 years; mean height=1.57±0.09 m; mean mass= 46.16±8.71 kg) and experimental group (14 girls; mean age=14.1±2.0 years; mean height=1.56±0.08 m; mean mass= 45.6±10.55 kg). The total number of time spending in training w`as 18 hours per week. Experimental group performed 2 hours plus of exercise with elastic cord. One of the aims of our study was to decide if we can observe differences between beginning and final measurements in experimental group. We used t-test for paired samples (p=0.006578; the significance level 95%). Therefore we can indicate our training programme with elastic cord as a way of improving postural stability in our group of elite gymnasts. - See more at: http://www.jhse.ua.es/jhse/article/view/802#sthash.CqnywX8V.dpuf